Penerapan Manajemen Risiko Pada Proses Pengembangan Properti Pada PT Gowa Makassar Tourism Developmen Tbk. - Palosong, Alosius Rinto; Kende, Aditia Saputri; Tangke, Meisy Wulandari; Tumimba, Yelvira Monica; Sabandar, Sita Yubelina; Mongan, Frischa Faradilla Arwinda (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore more deeply the application of risk management in the property development process at PT Gowa Makassar Tourism Development Tbk. Through this analysis, it is expected to provide insight for industry practitioners and academics about the importance of risk management in improving the success of property development. The data analysis method used is a descriptive qualitative method consisting of data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that risk management in property development at PT Gowa Makassar Tourism Development Tbk consists of the risk of unavailability of funding and credit risk, interest rates, increasingly fierce competition, market fluctuations and reputation, the benchmarks used are measuring, analyzing, and evaluating in their evaluation. Implementation of Risk Management Implementation of PT Gowa Makassar Tourism Development Tbk is carried out by conducting risk identification, risk analysis, risk mitigation, and regular review of business operations against key performance indicators. This should be important to be done by PT Gowa Makassar Tourism Development Tbk as a determinant of success so that this research is also expected to help the company PT Gowa Makassar Tourism Development Tbk in the property development process to minimize the risks that may arise from all business activities.